2014
DOI: 10.3389/fpls.2014.00647
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study on Ca content and distribution in two Gesneriaceae species reveals distinctive mechanisms to cope with high rhizospheric soluble calcium

Abstract: Excessive Ca is toxic to plants thus significantly affects plant growth and species distribution in Ca-rich karst areas. To understand how plants survive high Ca soil, laboratory experiments were established to compare the physiological responses and internal Ca distribution in organ, tissue, cell, and intracellular levels under different Ca levels for Lysionotus pauciflorus and Boea hygrometrica, two karst habitant Gesneriaceae species in Southwest China. In the controlled condition, L. pauciflorus could surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 52 publications
0
10
0
Order By: Relevance
“…The selected spots of the fruit sample were analysed using energy dispersive X-ray spectroscopy (EDS) with a Bruker X-ray detector equipped with a scanning electron microscope with operating conditions of the electron microprobe of 20 kV (SEM, Zeiss Ultra Plus, Oberkochen, Germany). At least five replicates of X-ray line scans were obtained for each sample, and then data analyses were carried out according to Li [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…The selected spots of the fruit sample were analysed using energy dispersive X-ray spectroscopy (EDS) with a Bruker X-ray detector equipped with a scanning electron microscope with operating conditions of the electron microprobe of 20 kV (SEM, Zeiss Ultra Plus, Oberkochen, Germany). At least five replicates of X-ray line scans were obtained for each sample, and then data analyses were carried out according to Li [ 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…Previous studies on the vegetation in the karst area showed that there are obligated calciferous plants that grow only in limestone areas 5 . Other researchers determined the calcium content and the exchangeable calcium content of the above ground and underground parts of common plants in various karst regions and found that 14 dominant species of karst ecosystem could be classified based on their aboveground and underground calcium content into high-calcium, low-calcium, and medium-calcium content plants 6,7 . High-calcium plants have a strong calcium-enrichment ability, and their above-ground parts can maintain high calcium content even in relatively low-calcium soils.…”
Section: Introductionmentioning
confidence: 99%
“…Ca 2+ measurements of leaf cells were performed as previously described (Li et al, 2014) with the following minor modifications: transverse sections of (5-10 mm) sugarcane ShGPCR1:OE and NT leaves were prepared using razor blades in Tyrode solutions (145-mM NaCl, 5-mM KCl, 2-mM CaCl 2 , 1-mM MgCl 2 , 10-mM Glucose, and 20-mM HEPES, pH 7.4) with 23 μM of the Ca 2+ -sensing dye Fluo-4 AM (Invitrogen™ Molecular Probes™, Eugene, OR, United States) and 2.5 μl of power concentrate (100x; Invitrogen™ Molecular Probes™) for 1 h at room temperature. Subsequently, leaf pieces were placed on a glass coverslip and visualized under an Olympus IX71 inverted microscope attached with PTI EasyRatioPro system (HORIBA Scientific, Piscataway, NJ, United States).…”
Section: Cellular Calcium Imaging and Measurementsmentioning
confidence: 99%